Two Distinctive Phenotypes of AcMNPV Display Different Immune Abilities and Intracellular Destiny - Molina, Guido Nicolás (2016)
The budded phenotype (BV) of the baculovirus AcMNPV has been demonstrated to have strong immunostimulatory properties that are relevant for the development of vaccines and antiviral therapies. Although the occluded phenotype (ODV) shares the main structural proteins and its genome with BV, it has been poorly studied in mammals. In this study, we assessed the capacity of ODV to induce immune responses in mice. In contrast to BVs, ODVs failed to promote the secretion of IFN-gamma, IL-6 and Il-12 and to induce antiviral activity against VSV in the short term. Furthermore, ODVs were unable to induce cellular immunity against a coadministered antigen 7 days after inoculation. By analyzing the interaction of ODVs with BMDCs, we observed that although ODVs entered the cells reaching late and acidic endosomes, they did not induce their maturation. Finally, we also analyzed if BVs and ODVs followed different routes in the cell during the infection. BVs, but not ODVs, colocalized with the protein ovalbumin in compartments with the presence of proteases. The results suggest that structural differences could be responsible for their different destinies in the dendritic cell and this could lead to a different impact on the immune response.